The Economic Journal the quarterly journal of the Royal Economic Society. (Macmillan, 1891)
Each volume of the Economic Journal feature: a selection of the best new work in theoretical and empirical economics, a new Policy Forum; an extensive book review section; regular specially-commissioned survey articles; and a regular Software Review section.